The AKIBAT HUKUM TERHADAP JUAL-BELI TANAH KAVELING YANG TIDAK BERIJIN: JUAL-BELI TANAH KAVELING - TRISNA DEWI NI MADE (VYAVAHARA DUTA, 2023)
The problem described in this research is about how the settlement efforts to buy and sell land that is not licensed kaveling and how the legal effect on the sale of land purchases that are not licensed. The purpose of writing this paper is to know the settlement of the sale of land purchases of land that is not licensed and can know the legal consequences of buying and selling of land that is not licensed kaveling. The research method used in this thesis is the type of normative research that is by focusing on the rules that apply as well as the literature or books related to the issues discussed. The result of his research is the settlement of the sale and purchase of land that is not licensed from the subject of sale and purchase caused by the unequal fulfillment of rights and obligations of parties in the sale and purchase of land plots, from the object of sale and purchase caused by technical procedures such as the application permit kaveling and splitting certificates that are not executed properly, the settlement efforts are adjusted to each of the obstacles that occur where the barriers of the subject of sale and purchase settled by the fulfillment of the rights and obligations of the parties first in a balanced, while the barriers of the object of sale and purchase is completed by the implementation of procedures the fastest in accordance with the laws and regulations. While the legal consequences for the sale and purchase of land that has no license for the parties who make transactions through binding agreements of land sale and sale will be difficult to publish the proof of ownership of land (certificate) in the process behind the name at the notary / PPAT office where the parties entered into an agreement binding sale and purchase of land. The legal power of the sale and purchase agreement and the power of attorney which follows the agreement depends on the form of the agreement.